Lipase-catalyzed enantioselective hydrolysis of methyl 2-fluoro-2-arylpropionates in water-saturated isooctane - Wang, Pei-Yun; Chen, Teh-Liang; Tsai, Shau-Wei; Cipiciani, Antonio; Bellezza, Francesca; Ruzziconi, Renzo (Journal of Molecular Catalysis B: Enzymatic, 2006)
Lipases from Candida rugosa, Candida antartica B and Carica papaya are employed as the biocatalyst for the hydrolytic resolution of methyl 2-fluoro-2-arylpropionates in water-saturated isooctane, in which excellent to good enantioselectivity without the formation of byproducts is obtained for the papaya lipase when using (R,S)-2-fluoronaproxen methyl ester (1) and methyl (R,S)-2-fluoro-2-(4-methoxyphenyl)propionate (2), but not methyl (R,S)-2-fluoro-2-(naphth-1-yl)propionate (3) as the substrates. The thermodynamic analysis indicates that the enantiomer discrimination for the papaya lipase is driven by the difference in activation enthalpy for compound 1, 2 or (R,S)-naproxen methyl ester (4). The kinetic analysis also demonstrates that in comparison with (S)-4, the insertion of the 2-fluorine moiety in (R)-1 has increased k(2), but not K-m, and consequently the lipase activity.